2022
DOI: 10.1186/s12968-022-00862-4
|View full text |Cite
|
Sign up to set email alerts
|

Imaging gravity-induced lung water redistribution with automated inline processing at 0.55 T cardiovascular magnetic resonance

Abstract: Background Quantitative assessment of dynamic lung water accumulation is of interest to unmask latent heart failure. We develop and validate a free-breathing 3D ultrashort echo time (UTE) sequence with automated inline image processing to image changes in lung water density (LWD) using high-performance 0.55 T cardiovascular magnetic resonance (CMR). Methods Quantitative lung water CMR was performed on 15 healthy subjects using free-breathing 3D sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 38 publications
0
32
0
Order By: Relevance
“…Note that the measurements were acquired on one single coronal slice that intersects the center of the descending aorta, and the different slices may result in different measurements due to gravitation dependence of lung water distribution. 26 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Note that the measurements were acquired on one single coronal slice that intersects the center of the descending aorta, and the different slices may result in different measurements due to gravitation dependence of lung water distribution. 26 …”
Section: Discussionmentioning
confidence: 99%
“…The R2$$ {R}_2^{\prime } $$ estimate from the proposed ES‐MCSE method shows less intersubject variance with higher precision than that from the reference methods. Note that the measurements were acquired on one single coronal slice that intersects the center of the descending aorta, and the different slices may result in different measurements due to gravitation dependence of lung water distribution 26 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6] MRI has recently been proposed as a promising method to noninvasively quantify lung water. 4,[7][8][9][10] MRI addresses some limitations of current clinical lung water assessments, which include invasive cardiac catheterization, semi-quantitative ultrasound, or ionizing radiation exposing computed tomography and x-ray. [11][12][13] Previous work has found that lung water MRI can depict a regional redistribution of edema, 9,14 and is associated with myocardial energetic deficits in heart failure with preserved ejection fraction (HFpEF).…”
Section: Introductionmentioning
confidence: 99%
“…4,[7][8][9][10] MRI addresses some limitations of current clinical lung water assessments, which include invasive cardiac catheterization, semi-quantitative ultrasound, or ionizing radiation exposing computed tomography and x-ray. [11][12][13] Previous work has found that lung water MRI can depict a regional redistribution of edema, 9,14 and is associated with myocardial energetic deficits in heart failure with preserved ejection fraction (HFpEF). 8 These previous studies acquired images at rest or shortly after exercise, but transient changes in lung water during exercise is yet to be imaged using MRI.…”
Section: Introductionmentioning
confidence: 99%